Comparative Pharmacokinetics Between a Fixed‐Dose Combination of Pitavastatin/Valsartan 4/160 mg and the Corresponding Individual Components Through a Partial Replicated Crossover Design in Healthy Male Subjects. Issue 5 (8th January 2022) - Na, Joo Young; Yang, Eunsol; Kim, Jae‐Hoon; Kwon, In Sun; Jin, Eun‐Heui; Yu, Kyung‐Sang; Kim, Jinsook; Lee, SeungHwan; Hong, Jang Hee
Abstract: Hypertension and hyperlipidemia are often comorbid, requiring combination therapies of antihypertensive drugs and antihyperlipidemia drugs. Taking 1 fixed‐dose combination (FDC) may increase patient compliance rather than taking each of the drugs separately. This study aimed to evaluate the pharmacokinetic bioequivalence between an FDC of pitavastatin/valsartan 4/160 mg and the corresponding individual components. Considering that valsartan is a highly variable drug for maximum plasma concentration (Cmax ), an open‐label, randomized, partial replicated crossover study was conducted in 54 healthy subjects. The subjects received a single oral dose of the FDC of pitavastatin/valsartan 4/160 mg in 1 period or the corresponding individual components in the other 2 periods. The geometric mean ratios and their 90%CIs of the FDC to the corresponding individual components for Cmax and area under the concentration‐time curve from time 0 to the last measurable time point were 1.05 (90%CI, 0.96‐1.15) and 0.10 (90%CI, 0.95‐1.04) for pitavastatin and 1.15 (90%CI, 1.06‐1.25) and 1.06 (0.99‐1.14) for valsartan, respectively. The geometric mean ratios (90%CIs) for area under the concentration‐time curve from time 0 to the last measurable time point and Cmax of both drugs were included in the bioequivalence criteria. In conclusion, the FDC of pitavastatin/valsartan 4/160 mg showed pharmacokinetic equivalence with the corresponding individual components.